2021
DOI: 10.1186/s12891-021-04885-3
|View full text |Cite
|
Sign up to set email alerts
|

Acromiohumeral distance and supraspinatus tendon thickness in people with shoulder impingement syndrome compared to asymptomatic age and gender-matched participants: a case control study

Abstract: Background Shoulder impingement syndrome (SIS) is the most common form of shoulder pain. Conservative and surgical treatments for SIS are often not effective. One such surgical intervention is subacromial decompression, aimed at widening the subacromial space (SAS). A better understanding of the changes in the SAS may help explain the relative ineffectiveness of current interventions. Objective: To measure the acromiohumeral distance (AHD) and supraspinatus tendon thickness (STT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
(76 reference statements)
0
5
1
1
Order By: Relevance
“…In another study, Bağcıer et al[ 27 ] performed AHD measurements on US in the shoulder impingement syndrome group and showed an intra- and interobserver correlation with a perfect confidence interval. Although the AHD values in their study were higher than ours, Hunter et al[ 29 ] showed that AHD increased with thickened tendons in patients with impingement syndrome, which may explain the high results of Bağcıer et al[ 27 ]…”
Section: Discussioncontrasting
confidence: 72%
“…In another study, Bağcıer et al[ 27 ] performed AHD measurements on US in the shoulder impingement syndrome group and showed an intra- and interobserver correlation with a perfect confidence interval. Although the AHD values in their study were higher than ours, Hunter et al[ 29 ] showed that AHD increased with thickened tendons in patients with impingement syndrome, which may explain the high results of Bağcıer et al[ 27 ]…”
Section: Discussioncontrasting
confidence: 72%
“…Individuals suffering from long‐term chronic overload strain on their shoulders and people who frequently perform overhead exercises develop considerable SUP thickening, inflammatory edema, and impingement, leading to shoulder pain and limited motion 13 . Hunter et al 14 reported that individuals with SIS had significantly higher AHD and SUP values. The linear regression model indicated an association between the AHD and SUP thickness, suggesting that when the SUP thickness increases in size, the AHD also increases.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this pattern could also decrease the subacromial space and thus increase the compressive load on the tendon, however, this hypothesis has been challenged. 21,22,71,73,74 There is limited research on muscle activation timing of the RC and deltoid muscles, as all the studies that have explored these muscles have only looked at EMG amplitude and found no consistent pattern. 118,145147,153,154,157…”
Section: Neuromuscular Factorsmentioning
confidence: 99%
“…Subacromial impingement is no longer considered the primary mechanism in RC tendinopathy now. 6,9,2125 Cross-sectional studies have explored supraspinatus tendon thickness in RC tendinopathy 22,23,50,7176 (see Supplemental Table 2). The majority of the studies report increased tendon thickness with RC tendinopathy.…”
Section: Tendon Structurementioning
confidence: 99%